(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The influence of geometric eccentricity on the oscillations of bevel gears is studied. A gear train consisting of two "exact" gears with axes offset from the geometric center is considered. A mathematical model is compiled through which the oscillations in the tooth engagement are studied. It is proved that the oscillations in the contact zone are described by the Mathieu equation. It turns out that the geometric eccentricity of bevel gears excites two types of oscillations - forced and parametric. Experimental results from a ship's power system are presented.